Back muscle strength and trunk extension: are they related in physical sport students? - Saputro, Deny Pradana; Abdullah, Nagoor Meera; Aliriad, Hilmy; Karo-Karo, Alan Alfiansyah Putra; Helmi, Boby (Universitas Negeri Surabaya, 2025)
This study aimed to determine the relationship between back muscle strength and trunk and neck extension ability in Physical Sport students. Back muscle strength was measured using a Back Dynamometer (Back-D), while trunk and neck extension ability was measured using an Extension Dynamometer (Extension-D). This study used a cross-sectional correlational design with a sample of 38 students who met the inclusion criteria. The measurement procedure was carried out twice for each instrument, and the highest value was used for analysis. The Shapiro–Wilk normality test showed that all data were normally distributed (p > 0.05). The linearity test produced an R² value of 0.0007, indicating no linear relationship between the two variables. The Spearman correlation test was then used and showed no significant relationship between back muscle strength and trunk and neck extension ability (ρ = –0.030; p = 0.860). The results of this study confirm that these two physical capacities are independent domains and do not directly influence each other. Thus, the Back-D and Extension-D cannot be used interchangeably in evaluating trunk function, and each instrument must be applied according to the measurement objectives.